2000
DOI: 10.1002/(sici)1098-2396(200007)37:1<64::aid-syn7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of the binding of the dopamine D2 receptor agonist11C-(R,S)-5-hydroxy-2-(di-n-propylamino)tetralin in rodents and nonhuman primate

Abstract: The in vitro autoradiographic binding characteristics as well as in vivo imaging characteristics of a dopamine D2 receptor agonist, (R, S)-2-(N-propyl-N-1'-(11)C-propyl)amino-5-hydroxytetralin ((11)C-5-OH-DPAT), were studied. In (3)H-spiperone assays using rat striata, 5-OH-DPAT exhibited an affinity of IC(50) = 2.5 nM. In vitro autoradiographs in rat brain slices with (11)C-5-OH-DPAT revealed selective binding to the dopaminergic regions in the striata which was displaceable by sulpiride. Varying concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Like PHNO, 3 H‐PD128907 is likely a D3R preferred radioligand with a high liklihood of binding to D2 high sites as well. Similarly, we have reported 11 C‐5‐OH‐DPAT and 18 F‐5‐OH‐FPPAT, which bind to striatum in vitro and in vivo and are sensitive to Gpp(NH)p and are considered as D2R high binding agents (Mukherjee et al, ; Shi et al, ). The D3R component of these derivatives have yet to be determined.…”
Section: Evidence Of D3 Receptors Using Imaging Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…Like PHNO, 3 H‐PD128907 is likely a D3R preferred radioligand with a high liklihood of binding to D2 high sites as well. Similarly, we have reported 11 C‐5‐OH‐DPAT and 18 F‐5‐OH‐FPPAT, which bind to striatum in vitro and in vivo and are sensitive to Gpp(NH)p and are considered as D2R high binding agents (Mukherjee et al, ; Shi et al, ). The D3R component of these derivatives have yet to be determined.…”
Section: Evidence Of D3 Receptors Using Imaging Methodsmentioning
confidence: 79%
“…The binding of 7‐OH‐DPAT to the uncoupled D2R low‐affinity (D2 low ) sites was found to be too low (Gonzalez and Sibley, ). We have previously shown that 11 C‐5‐OH‐DPAT is able to penetrate the rodent and nonhuman primate brain (Mukherjee et al, ). Uptake of 11 C‐5‐OH‐DPAT in the rat brain was ∼1% of the injected dose.…”
Section: Discussionmentioning
confidence: 97%
“…Several agonists have been pursued for in vivo imaging. Aminotetralins, 11 C‐5‐OH‐DPAT, 11 C‐PPHT, 11 C‐ZYY339, and 18 F‐5‐OH‐FPPAT have been reported by us for successful PET imaging of dopamine receptors (Mukherjee et al, ; Shi et al, ). Depending on the position of the phenolic hydroxyl (5‐ or 7), the aminotetralins can exhibit higher affinity for D2 while maintaining a similar affinity for D3 receptors (Figure , 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, all D 2/3 radioligands used in human PET or SPECT studies are radio-labelled antagonists, which do not differentiate between D 2 high and D 2 low . Several research groups have recently reported on development and experimental use of newly developed D 2/3 agonist radioligands (Zijlstra et al, 1993a, b;Shi et al, 1999Shi et al, , 2004Hwang et al, 2000;Mukherjee et al, 2000Mukherjee et al, , 2004Finnema et al, 2005;Narendran et al, 2004). Similar to dopamine, D 2/3 agonist radioligands are expected to bind mainly to D 2 high .…”
Section: Introductionmentioning
confidence: 99%